Problems of Tax Collection by the Tax Mafia in the Perspective of Tax Law - Gevan Naufal Wala; Rasji Rasji (CV. Rayyan Dwi Bharata, 2023)
This journal will explain further about the tax mechanism that takes place in the tax collection process and also the provisions related to the tax sustainability mechanism so far. Tax collection can result in tax disputes between taxpayers and tax collectors. According to Law Number 14 of 2002 concerning the Tax Court (hereinafter referred to as the Tax Court Law) Article 1 number 5 states that a tax dispute is a dispute that arises in the field of taxation between a taxpayer or tax bearer and an authorized official as a result of the issuance of a decision that will filed an appeal or lawsuit to the tax court based on taxation laws and regulations, including lawsuits for the implementation of billing based on the Tax Collection Law with a forced letter. To maximize profits and avoid losses, taxpayers do tax evasion intentionally. This is due to the lack of concern for the state. The absence or lack of public awareness about taxpayers paying taxes to the state is a form of resistance. The importance of paying taxes, the benefits of paying taxes, and the sanctions that will be imposed if non-compliant taxpayers are not socialized by the government to the public as taxpayers. Therefore, regulations and sanctions related to tax avoidance need to be emphasized in order to provide a deterrent effect for tax avoiders.